Mitigating lack of knowledge: a study of ideas in innovative projects. Issue 3 (1st October 2016) - Karlsson, Anna; Törlind, Peter
Abstract : Ideas and concepts are the carriers of innovation, which many regard as a critical source of competitive advantage. At the same time, an initial idea is untested and unrealized, i.e., it is always surrounded by a lack of knowledge. The purpose of this paper is to investigate how different types of ideas develop and interact with knowledge, by focusing on remediating activities performed by design teams. Results are based on a retrospective interview study involving respondents from eight projects, all selected for their high degree of innovativeness. The analysis emphasized two types of ideas (product ideas and concept ideas) and three spaces of design knowledge (the why-space, the what-space, and the how-space). The results reveal two possibilities: either the content of the knowledge space differs depending on the type of idea, or different knowledge spaces exist. Moreover, activities conducted to improve the idea have different characteristics depending on the type of idea. It is thus important to distinguish between different types of ideas and to choose corresponding mitigation activities to support idea development.